2007
DOI: 10.1111/j.1365-3121.2007.00744.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of methane seeps on the local carbon‐isotope record: a case study from a Late Jurassic hemipelagic section

Abstract: An Oxfordian (Late Jurassic) hemipelagic succession from Beauvoisin (SE France) contains a pronounced, short‐lived negative excursion in the bulk‐carbonate carbon‐isotope record, with an amplitude of 4‰. It was shown previously that the Beauvoisin paleoenvironment was impacted by hydrocarbon seepage. New isotopic data corroborate that methane was a significant constituent of these hydrocarbons. The negative excursion was caused by transient enhanced precipitation of 13C‐depleted carbonate, mediated by anaerobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…One of the best‐studied Jurassic methane seeps formed during Oxfordian time ( ca 160 Ma) at Beauvoisin, south‐east France (Peckmann et al ., ). Highly depleted δ 13 C carb values of down to −30‰ in calcite nodules within the Oxfordian section probably result from hydrocarbon‐sourced methane seepage (Louis‐Schmid et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…One of the best‐studied Jurassic methane seeps formed during Oxfordian time ( ca 160 Ma) at Beauvoisin, south‐east France (Peckmann et al ., ). Highly depleted δ 13 C carb values of down to −30‰ in calcite nodules within the Oxfordian section probably result from hydrocarbon‐sourced methane seepage (Louis‐Schmid et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…V and U both have in common that there is no detrital influence to their concentration in marine sediments. As already mentioned above, the turning point of the isotope excursion coincides with a major change in the Tethyan sedimentation pattern [1][2][3]. This was also the time of a profound rearrangement of the oceanic current system induced by the establishment of a new circum-global ocean passage in low latitudes.…”
Section: Discussionmentioning
confidence: 56%
“…the positive 13 C excursion senso stricto). Again, this correlation of the 13 C excursion with trends in Ti, Nb, and W as well as Mn and Fe contents seems to reflect changes in the Oxfordian palaeooceanography and climate [1][2][3][4]. The climate during the late Oxfordian was dominated by warm and arid conditions.…”
Section: +mentioning
confidence: 81%
See 1 more Smart Citation
“…However, the finding of accumulated isotopically light archaeol, in combination with barite and dolomite enrichments, supports the concept that these signatures instead represent the imprint of a former SMT (Contreras et al, 2013) [59] and are thus a diagenetic feature. Similarly, Louis-Schmid et al (2007) [114] found that a 4% negative excursion in a Late Jurassic hemipelagic succession at Beauvoisin (SE France) is the result of local anaerobic methane oxidation and precipitation of authigenic carbonates, rather than a global signal.…”
Section: Diagenetic Vs Atmospheric Signatures?mentioning
confidence: 97%